An Exploration of Motivations for Women Mine Workers to Work Underground. (July 2021) - Ledwaba, Sally; Nkomo, Thobeka S.
Women have previously been discouraged from pursuing careers in the mining industry given the intense nature of the work in the field and societal norms. However, with the attainment of democracy in South Africa, new legislative frameworks were introduced which advocated for women to not be discriminated against working underground. This article, therefore, focused on exploring the motivations of 10 underground woman mine workers to pursue careers in the mining industry despite the masculine work culture which is deemed exclusionary to women. The article used semi-structured interviews to collect data. Data collected from participants were analyzed using thematic analysis, in conjunction with the literature reviewed. The article unraveled that although the new democratic dispensation has tried to make the mining industry attractive to women, many of them went into the industry as a result of their economic and social circumstances.